EVALUATING THE AQUATIC HEALTH: A COMPREHENSIVE STUDY OF PHYSICO-CHEMICAL PROPERTIES OF UJANI RESERVOIR, MAHARASHTRA - Digvijay Kumbhar,; Lazarus Lanka,; Dnyandeo Mhaske, (The Bioscan, 2025)
The Ujani Reservoir serves as a primary water source for the Pune, Ahilyanagar, and Solapur districts, fulfilling various needs such as agriculture, small-scale industries, electricity generation, drinking water, fishing, and tourism. Over a two-year period, from November 2021 to September 2023, we conducted a bimonthly analysis of the physico-chemical parameters of water, including temperature, pH, total dissolved solids (TDS), alkalinity, calcium hardness, magnesium hardness, total hardness, nitrates, chlorides, phosphates, dissolved oxygen (DO), and biochemical oxygen demand (BOD). This study involved fifteen different sampling sites, including backwater wetland areas along the Bhima River basin and the catchment area of the Ujani Reservoir. The selected sites for this research were Daund (S-1), Ajnuj-Devulgaon (S-2), Pedgaon (S-3), Baradgaon Sudrik (S-4), Khed-Shimpora (S-5), Rajegaon-Bhigwan (S-6), Khanota (S-7), Diksal (S-8), Kondhar Chincholi (S-9), Kumbhargaon (S-10), Dalaj (S-11), Palasdeo (S-12), Parewadi (S-13), Chikhalthan No.1 (S-14), and Shiral (S-15). Our findings revealed that many of the physico-chemical parameters at several sampling sites exceeded the permissible limits set by IS, ICMR, BIS, and WHO, indicating that the water quality is unsuitable for both drinking and irrigation purposes. Seasonal variations in these physico-chemical parameters significantly influence the biological communities in and around the water bodies, as well as the biodiversity of aquatic birds.